SybilSCAR: Sybil detection in online social networks via local rule based propagation - Binghui Wang; Le Zhang; Gong, Neil Zhenqiang (IEEE INFOCOM 2017 - IEEE Conference on Computer Communications, 2017)
Detecting Sybils in online social networks (OSNs) is a fundamental security research problem as adversaries can leverage Sybils to perform various malicious activities. Structure-based methods have been shown to be promising at detecting Sybils. Existing structure-based methods can be classified into two categories: Random Walk (RW)-based methods and Loop Belief Propagation (LBP)-based methods. RW-based methods cannot leverage labeled Sybils and labeled benign users simultaneously, which limits their detection accuracy, and they are not robust to noisy labels. LBP-based methods are not scalable, and they cannot guarantee convergence. In this work, we propose SybilSCAR, a new structure-based method to perform Sybil detection in OSNs. SybilSCAR maintains the advantages of existing methods while overcoming their limitations. Specifically, SybilSCAR is Scalable, Convergent, Accurate, and Robust to label noises. We first propose a framework to unify RW-based and LBP-based methods. Under our framework, these methods can be viewed as iteratively applying a (different) local rule to every user, which propagates label information among a social graph. Second, we design a new local rule, which SybilSCAR iteratively applies to every user to detect Sybils. We compare SybilSCAR with a state-of-the-art RW-based method and a state-of-the-art LBP-based method, using both synthetic Sybils and large-scale social network datasets with real Sybils. Our results demonstrate that SybilSCAR is more accurate and more robust to label noise than the compared state-of-the-art RW-based method, and that SybilSCAR is orders of magnitude more scalable than the state-of-the-art LBP-based method and is guaranteed to converge. To facilitate research on Sybil detection, we have made our implementation of SybilSCAR publicly available on our webpages.